Association between neighborhood disadvantage and chronic hepatitis B in the central Puget Sound region of Washington, 2018 to 2023 - Grace Dickel; Kristine Lan; Christine Khosropour; H. Nina Kim (PLoS ONE, 2026)
Background Chronic Hepatitis B (CHB) disproportionately affects immigrant and socioeconomically marginalized populations in the United States. Neighborhood-level metrics such as the Area Deprivation Index (ADI) may provide insight into structural and geographic indicators of CHB risk. Methods and findings We used electronic health record data from the University of Washington Medicine system to assess the association between neighborhood-level social deprivation and a positive CHB status among adults aged ≥18 with at least one clinical encounter between 2018 and 2023. We conducted a case-control study where CHB cases were identified via positive hepatitis B surface antigen or detectable HBV DNA. Comparators were selected from patients who had a complete blood count (CBC) or chemistry panel testing as a general marker of healthcare engagement to ensure comparable opportunity for diagnosis. The comparators were then frequency matched to cases by care setting and calendar year quarter of medical encounter. Geocoded patient billing addresses were linked to census block groups to confer ADI scores, which were analyzed in 2-, 5-, and 10-level categories. Finer ADI stratification better captured gradients in neighborhood disadvantage and revealed the clearest trends; results from the 10-level ADI categories are noted here. Logistic regression models adjusted for age, sex, race, ethnicity, and insurance status were used to estimate odds ratios (OR) for CHB cases across ADI categories. The final study cohort included 5,729 CHB cases and 6,143 comparators. CHB was more common among individuals identifying as Asian, Black, or Native Hawaiian/Pacific Islander, and those with public or no insurance. Adjusted models showed higher odds of a CHB positive test among residents of more disadvantaged neighborhoods, with the highest ADI category associated with twice the odds of CHB compared to the least disadvantaged category (adjusted OR = 2.07, 95% CI: 1.51–2.82), with an overall upward trend across ADI levels. Conclusions Neighborhood-level disadvantage was associated with higher odds of a CHB positive test when using granular stratification of ADI and after adjusting for individual-level factors. These findings support the integration of place-based metrics to inform targeted public health initiatives, including community-responsive education, and geographically focused hepatitis B screening and linkage-to-care efforts in socially disadvantaged neighborhoods.